2018
DOI: 10.2136/sssaj2017.06.0193
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Iron Reduction Increases with Rainfall in Montane Basaltic Soils of Hawaii

Abstract: In upland soils, the potential for iron reduction to occur increases with rainfall. Bulk soil anoxia is not a requirement for soil iron reduction. Soil iron reduction likely occurs at most sites that experience periodically high soil moisture. Microbe‐mediated Fe reduction modulates the role of Fe‐bearing minerals, and can occur without saturation, in upland soils. Quantifying this Fe reduction is difficult, but critical for identifying climates in which Fe reduction plays a role in soil biogeochemistry. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
3
12
0
Order By: Relevance
“…The Upland deep zone did not see significant paint removal. In the first 22 d there was 6% removal, but following a rain event, which saturated the deep zone, paint removal increased to 27% in the subsequent 6 d. In all cases, paint removal rates were higher during periods of saturation, consistent with other IRIS studies that show rainfall events can induce iron reduction (Hodges et al, 2018) and soil saturation is the main factor affecting iron-oxide paint removal (Bryant, 2010). One other factor, necessary for microbial activity responsible for paint removal, is a labile C source.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The Upland deep zone did not see significant paint removal. In the first 22 d there was 6% removal, but following a rain event, which saturated the deep zone, paint removal increased to 27% in the subsequent 6 d. In all cases, paint removal rates were higher during periods of saturation, consistent with other IRIS studies that show rainfall events can induce iron reduction (Hodges et al, 2018) and soil saturation is the main factor affecting iron-oxide paint removal (Bryant, 2010). One other factor, necessary for microbial activity responsible for paint removal, is a labile C source.…”
Section: Resultssupporting
confidence: 86%
“…Rainfall changed both the soil temperature (Supplemental Figure S6) and the degree of soil water saturation in the target zone (0-30 cm bgs; Figure 4). Metal-oxide paint removal rates fit the expected pattern based on soil saturation (Hodges et al, 2018); higher saturation resulted in higher removal rates (Table 1). Iron-oxide tubes (r 2 range: .71-.94) and manganese-oxide tubes (r 2 range: .48-.84) fit a linear model (Table 1).…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Under shifting climate regimes, intense storms that saturate soil are anticipated to become more frequent (Greve et al, 2014), and this increased precipitation has been demonstrated to stimulate Fe-reducing conditions, even under bulk oxidizing conditions in soils (Hodges et al, 2018). Therefore, it is likely that under these future rainfall predictions the proportion of anaerobic respiration contributing to total soil C flux will increase (Keiluweit et al, 2016(Keiluweit et al, , 2017.…”
Section: Implications: Role Of Anaerobic Respiration In the Carbon Cymentioning
confidence: 99%
“…This suggests that rainfall does not have an immediate impact on Fe and C biogeochemistry, but rather it is the accumulation of water in the soil (soil moisture) that has a rapid impact on these parameters; reinforcing that soil moisture drives biogeochemical cycling, not rainfall. Additionally, elevated soil moisture content had a strong relationship with the potential for Fe reduction as measured by uniformly oxidized steel rods (i.e., Indicator of Reduction in Soils-IRIS) deployed across a topographic gradient in volcanic soils from Hawaii [76], and also in upland Fe-rich and weathered soils from the United States (USA) southeastern piedmont [77]. In these studies, Fe reduction was likely stimulated by exogenous C inputs (such as DOC).…”
Section: Soil Moisture and Precipitation Influence Fe-c Redox Cyclingmentioning
confidence: 99%